2020
DOI: 10.5902/2236583443186
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico do doador voluntário de sangue em um hospital universitário no Rio de Janeiro

Abstract: Objetivo: Identificar o perfil epidemiológico dos doadores que compareceram ao processo de seleção pré-doação no Serviço de Hemoterapia do Hospital Universitário Pedro Ernesto. Método: Trata-se de um estudo seccional, exploratório descritivo, com abordagem quantitativa e análise estatística. Utilizou-se questionário auto aplicado para obtenção de variáveis que caracterizaram do perfil epidemiológico. Resultados: Dos 304 respondentes, 51,6% eram do sexo feminino; 42,1% tinham entre 20 e 29 anos, 66,5% eram natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…In Santa Catarina, in a study with 14,517 donors, 54.1% were men.8 Other studies corroborate the findings of this study, finding a higher prevalence of male candidates.9-10 In contrast to these findings, other studies carried out in the Federal District and Rio de Janeiro also found a higher prevalence of women. [11][12] Most donors were 20 to 29 years old; younger groups are more likely to donate blood voluntarily. 13 In a survey in Rio de Janeiro, for example, 73.8% of the donors were young people under 39 years old.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Santa Catarina, in a study with 14,517 donors, 54.1% were men.8 Other studies corroborate the findings of this study, finding a higher prevalence of male candidates.9-10 In contrast to these findings, other studies carried out in the Federal District and Rio de Janeiro also found a higher prevalence of women. [11][12] Most donors were 20 to 29 years old; younger groups are more likely to donate blood voluntarily. 13 In a survey in Rio de Janeiro, for example, 73.8% of the donors were young people under 39 years old.…”
Section: Discussionmentioning
confidence: 99%
“…13 In a survey in Rio de Janeiro, for example, 73.8% of the donors were young people under 39 years old. 12 However, a survey carried out only with elderly blood donors, argued that the recruitment should not focus only on the young, because in some cases, older individuals may present more requirements needed to donate when compared to the young. 14 As for race/color and marital status, whites and singles stood out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A idade do grupo estudado variou entre 18 a 21 anos por isso são considerados potenciais doadores de sangue e de medula óssea e poderão realizar as doações por um grande período de vida. Estudos realizados em outras regiões do país demonstram que o público entre 18 a 29 anos representam de 30 a quase 50% dos doadores de sangue (Costa et al, 2020;T. R. da Silva et al, 2021) e, segundo o Ministério da Saúde nesta faixa etária encontra-se 33% dos doadores de sangue no Brasil (Ministério da Saúde, 2022).…”
Section: Discussionunclassified
“…Thus, individuals now have more freedom, resulting in multiple partners, several sexual relationships and intercourse, and a decrease in the use of condoms. Such habits are frequent now, mainly among young adults 26 . Understanding the causes of blood donation refusal is essential to create adequate preventive strategies for the identified conditions and promote collective health.…”
Section: Discussionmentioning
confidence: 99%